Effect of Beer/Red Wine Marinades on the Formation of Heterocyclic Aromatic Amines in Pan-Fried Beef - Armindo Melo (2008)
The effect of beer or red wine marinades on the reduction of heterocyclic aromatic amines (HAs) formation in pan-fried beef was compared. The cooking experiments were performed under well-controlled temperature and time conditions. The samples were analyzed for HAs contents using solid-phase extraction and high-performance liquid chromatography-diode array detection/fluorescence detection. Unmarinated samples cooked in similar conditions provided reference HAs levels. Marinating with beer or with red wine resulted in decreased levels of HAs. The amount of 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine and 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline reduced significantly, respectively, around 88 and 40% after 6 h of marinating with beer or with wine. High variations were observed for reductions of A alpha C, ranging between 7 and 77%. Only beer marinade significantly reduced the levels of 4,8-DiMelQx at 1, 2, and 4 h of marinating. Multivariate statistical treatment of results indicated that beer can be more efficient on the reduction of some HAs formation. In addition, results from descriptive sensory analysis of unmarinated and 2 h marinated beef samples, tested for by two trained sensory panels, pointed to beer marinade as the most adequate for maintaining the usual overall appearance and quality of the pan-fried steaks.